Variations in Indonesian Translations of English AI Terms - Raden Roro Shinta Felisia (International Journal Multidisciplinary Science, 2025)
Artificial Intelligence (AI) is recognized for its speed and accessibility. It is rapidly spreading as people incorporate its functions into daily activities, such as searching for information, purchasing necessities, and designing models. Alongside the development of AI, Indonesian translations for AI terms have emerged. This study explores the variations in Indonesian translations of English AI terms. The results show that out of ten (10) English AI terms, three (3) translated terms are found on both the Pasti and Google websites. Meanwhile, the remaining seven (7) translated terms are not available on Pasti but are found on the Google website. Even when translating the same AI term, the Pasti and Google websites show variation. These variations include a partial-word (1 term), a full-word (1 term), and a letter (1 term), highlighting the diversity in Indonesian translations of English AI terms. This study is expected to contribute to the enrichment of the Indonesian AI terminology glossary.